Assessment of metro-induced vibrations on photo-voltaic modules for their solar energy degradation potential. (1st May 2023) - Bhore, Chaitanya V.; Andhare, Atul B.; Padole, Pramod M.; Loyte, Akshay; Yuvarajan, Devarajan; Thandavamoorthy, Raja; Ravikumar, J.
Highlights: Induced vibrations deteriorate the performance of solar Photo-Voltaic module. Vibrations were recorded and analyzed for different locations near metro. Recorded vibration levels were compared with FTA limits. Vibration measurement results were in good correlation with the literature.Induced vibrations and PV modules' natural frequencies fall in the same range. Abstract: Structures in the vicinity of elevated, surface and subway metro trains are subjected to induced vibrations generated due to train movements. Nowadays PV (Photo-Voltaic) modules are heavily installed in the vicinity of metro rail. These metro vibrations are induced in PV modules mounted on adjacent structures, which accelerates the formation of cracks and micro-cracks in PV cells. PV modules show a detrimental effect on their performance and life due to these cracks. Therefore, to understand the vibration levels, this study aims to find out the frequency content and amplitude of vibrations at different locations in the metro vicinity. Vibrations are recorded at locations such as metro tracks, stations (elevated and ground), and adjacent buildings/structures where solar PV systems are installed. Vibrations induced in the nearby structures show peak velocity amplitudes in the frequency range of 20–250 Hz. In conclusion, the vibrations in the vicinity of the metro train are below the FTA limits. However, PV modules' natural frequencies and induced vibrations fall in the same frequency range. This study shows that even when the induced vibrations are below the FTA limit, they can still cause a damaging effect on the PV modules, hence degrading solar energy generation.